An experimental viewpoint on the information depth of EBSD. Issue 2 (6th August 2015) - Wisniewski, Wolfgang; Rüssel, Christian
Summary: This article contains a critical review of the literature concerning the information depth of electron backscatter diffraction (EBSD) and a viewpoint on the topic is formulated. EBSD is applied to a crystal partially covered by a wedge of amorphous glass. EBSD‐patterns of decreasing quality are obtained from a crystal covered by an increasingly thick layer of glass. The location of the last indexable EBSD‐patterns is compared to the last discernible contrast in SEM‐micrographs obtained from the same crystal using accelerating voltages of 2–20 kV. It is concluded that the information depth of EBSD is at least as large as that of an SEM‐micrograph obtained with a voltage of 4 kV from a non‐tilted sample. Concepts of the information depth and experimental approaches are discussed. SCANNING 38:164–171, 2016. © 2015 Wiley Periodicals, Inc.